FAKTOR-FAKTOR PENGHAMBAT PERILAKU PENGELOLAAN KEUANGAN PETANI KELAPA SAWIT DI DESA AMBOYO INTI KABUPATEN LANDAK - Anita, Anita; Ulfah, Maria; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The aim of this research is to analyze the factors inhibiting the financial management behavior of oil palm farmers in Amboyo Inti Village. The subjects in this research consisted of nine oil palm farmers. This research uses a qualitative method with a case study approach. Data collection techniques were carried out in three ways, namely interviews, observation, and documentation. Data analysis techniques use data reduction, data presentation, drawing conclusions, and verification. The data validity checking technique uses triangulation technique. The results of the research show that the factors inhibiting the financial management behavior of oil palm farmers are financial knowledge, financial attitudes, and locus of control. Knowledge that hinders farmers in managing familly finances can be seen from informants who have difficulty dealing with emergency situations, have difficulty understanding finansial products, and do not understand loan interst. Apart from knowledge, financial attitude are also an obstacle for farmers in managing their familly finances, which can be seen from informants who use their money to buy things that are not very important, are wasteful and have an attitude that underestimates debt. Locus of control is also an obstacle to financial management of farming families. This can be seen from the results of interviews showing that informants have dificulty controlling income and expenses,